"As [Healthy] Women Should": Enslaved Women, Medical Experts, and "Hidden" Menstrual Disorders in Late Medieval Mediterranean Slave Markets. - Blumenthal, Debra (American Historical Review, 2023)
Expanding the discussion highlighting the role of slavery in the production of medical knowledge beyond the much more extensively studied Atlantic world and the nineteenth-century US South, this article explores the exploitation of enslaved women's bodies as clinical subjects in fifteenth-century Iberia. Menstrual disorders figured prominently among "hidden defects" cited in slave warranty suits filed by disgruntled buyers across the late medieval Mediterranean world. Reflective of their heightened interest in female physiology during this period, university-trained male physicians were the expert witnesses most frequently called on to resolve disputes concerning what an enslaved woman's lack of menses meant. Through a close analysis of "expert" testimony in seven lawsuits filed before the court of the Justicia Civil in Valencia in the 1440s, the slave market emerges as a site offering unparalleled opportunities for physicians to directly touch and probe female genitalia. Insofar as they could be poked and prodded with relative impunity, the bodies of enslaved women bought and sold in late medieval Mediterranean markets were instrumental to the expansion of learned gynecological knowledge.